Education and Training for Work in Argentina: Resignificance and Challenges in the Perspective of Youth and Adults - Riquelme, Graciela C.; Herger, Natalia (Education Policy Analysis Archives, 2005)
This paper argues that the combined effects of the criticisms to the Welfare State"s inefficiency and poor performance, the introduction of "modernizing policies" and market mechanisms handicapped the Argentinean system of adult education causing its diversification and dispersion. In order to analyze the impact of these processes of diversification and dispersion for the adult education and job training sectors, the authors conducted, volume quantification analyses taking into account educational demand (served and not-served) and its relationship with the public sector"s expenses in education and social programs. Finally, this article discusses the use of resources for social policies and their possible reorientation to attend genuine demands of popular sectors.